Fine-Tuning Circadian Rhythms: The Importance of Bmal1 Expression in the Ventral Forebrain - Mieda, Michihiro; Hasegawa, Emi; Kessaris, Nicoletta; Sakurai, Takeshi (Frontiers in Neuroscience, 2017)
Although the suprachiasmatic nucleus (SCN) of the hypothalamus acts as the central clock in mammals, the circadian expression of clock genes has been demonstrated not only in the SCN, but also in peripheral tissues and brain regions outside the SCN. However, the physiological roles of extra-SCN circadian clocks in the brain remain largely elusive. In response, we generated Nkx2.1-Bmal1-/- mice in which Bmal1, an essential clock component, was genetically deleted specifically in the ventral forebrain, including the preoptic area, nucleus of the diagonal band, and most of the hypothalamus except the SCN. In these mice, as expected, PER2::LUC oscillation was drastically attenuated in the explants of mediobasal hypothalamus, whereas it was maintained in those of the SCN. Although Nkx2.1-Bmal1-/- mice were rhythmic and nocturnal, they showed altered patterns of locomotor activity during the night in a 12:12-h light:dark cycle and during subjective night in constant darkness. Control mice were more active during the first half than the second half of the dark phase or subjective night, whereas Nkx2.1-Bmal1-/- mice showed the opposite pattern of locomotor activity. Temporal patterns of sleep-wakefulness and feeding also changed accordingly. Such results suggest that along with mechanisms in the SCN, local Bmal1–dependent clocks in the ventral forebrain are critical for generating precise temporal patterns of circadian behaviors.